Profiling protein hydrolysis and amino acid metabolism in camel and bovine milk fermented by Lactobacillus helveticus, L. bulgaricus, and Streptococcus thermophilus - Santhoshani Warakaulle; Mutamed M. Ayyash; Afaf Kamal-Eldin (Scientific Reports)
Abstract Fermented milk has received significant attention due to its multiple health benefits. The fermentation of milk is a complex and dynamic process that is greatly affected by the selection of the starter cultures. This study examined the impacts of mono- and co-fermentation involving Lactobacillus helveticus, L. delbrueckii subsp. bulgaricus, and Streptococcus salivarius subsp. thermophilus on proteolysis and amino acid metabolism in camel milk (CM) and bovine milk (BM). Fermentation of CM was accompanied by more degradation of caseins and formation of free amino groups compared with BM. Two-way ANOVA analysis showed that residual caseins and free amino group content are affected by bacteria, milk type, and their interactions (p < 0.001). Metabolomic analysis revealed variations in the amino acid metabolites between CM and BM including 12 free amino acids, 13 dipeptides, 12 tri- and higher peptides, and 7 lactoyl amino acids. Importantly, proline-rich peptides, known for their angiotensin-converting enzyme (ACE) inhibitory activity, were more abundant in CM and BM fermented with L. helveticus. These insights into milk differences and proteolytic system variations across bacterial cultures support the selection of strains with enhanced metabolic potential for fermented functional foods.